A comparative study of Dexmedetomidine and Dexamethasone as Adjuvants for Ultrasound-Guided Transversus Abdominis Plane Block in Total Laparoscopic Hysterectomy - Dr. Sahana P R, Dr. P. G. Raghavendra (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Transversus abdominis plane(TAP) block is widely used for postoperativeanalgesia in laparoscopic hysterectomy.Various adjuvants have been explored toprolong local-anaesthetic action, including dexmedetomidine and dexamethasone